Feasibility and complications in bipolar resectoscopy: Preliminary experience. Issue 1 (February 2013) - Mencaglia, Luca; Carri, Giada; Prasciolu, Claudia; Giunta, Giuliana; Albis Florez, Edmundo Daniel; Cofelice, Vito; Mereu, Liliana
Abstract Objective: To evaluate whether the new bipolar resectoscope (BR) 22 Fr (Karl Storz) represents a reliable improvement in operative hysteroscopy and to compare the new device to the 26 Fr BR (Karl Storz). Material and methods: A prospective observational study. From June 2010 through May 2011, 158 consecutive patients treated with bipolar resectoscope 22 Fr and 26 Fr for endocavitary pathologies were registered. Data analysis included patients'characteristics, surgical indications, operative time and complications. 140 patients were eligible. Results: 115/140 (82.1%) patients were treated by BR 22; 55 (39.2%) metroplastics, 34 (24.2%) polipectomies, 25 (17.8%) myomectomies and one (0.71%) sinechiolisis were performed. 25/140 (17.8%) patients were treated by BR 26; 6 (4.2%) polipectomies and 19 (13.5%) myomectomies were performed. Mean time of cervical dilatation by Hegar series was 57 sec for BR 22 Fr and 102 sec for BR 26 Fr (p = 0.034). 4/25 (16%) with 26BR and 1/115 (0.8%) with 22BR complications were observed (p = 0.002) : One uterine perforation, two post operative bleedings > 7 days, one intravasation syndrome and one cervical laceration. Conclusion: Bipolar resectoscopy is feasible and safe. The new device BR 22 Fr is preferable to 26 Fr because it requires lower cervical dilatation limiting operative time and complications.